The Reality of Using Educational Methods in Teaching Psychology to University Students from the Point of View of a Teacher at Salahaddin University - Aryan Hussein Sulaiman Dzaiy; Zuber Shareef Awla; Muhamad Muhyadin Sadiq (Zanco Journal of Human Sciences, 2024)
The current research aims to identify the extent of the availability of educational devices at the university and to reveal the reality of university teaching staff’s use of educational aids. The research also aims to identify the difficulties of using these educational devices and aids. The research community or population consists of 2180 male and female teachers at Salahaddin University - Erbil. The research community was chosen A random sample consisting of 105 faculty members was chosen. Those were specializing in psychology and teaching methods in 3 colleges, namely College of Education, College of Arts, and College of Basic Education. The scale of Qadi (2007) was relied upon, which consists of 4 domains and 44 items. The apparent validity of the scale was verified by presenting it to a group of 7 experts and arbitrators. The reliability of the scale was 0.82. The scale was then applied to the selected sample and appropriate statistical methods were applied to the data to extract the results. The results showed the university teaching staff’s use of educational media at different levels, as well as the existence of difficulties among university teaching staff in using educational media in general. The lack of training courses for teaching staff on producing and developing educational media ranked first among the difficulties. In light of the results, some recommendations and proposals were presented